Influential Article Review - Impact on Entrepreneurial Growth of Foreign Marketing Environments - Flores, Rosie; Gomez, Bridget; Phelps, Suzanne (Journal of Marketing Development and Competitiveness, 2019)
This paper examines entrepreneurship and marketing. We present insights from a highly influential paper. Here are the highlights from this paper Entrepreneurs all over the world seek ways of introducing their products to international markets; unfortunately, the international marketing environment poses a lot of opportunities and threats to foreign entrants. The cultural, political, and technological environments act as determinant factors in entrepreneurial success in global markets. This study aims to unravel the effects of these international marketing environments on entrepreneurial developments. The study being descriptive and historical relied heavily on secondary sources of information. Analysis revealed that the PESTEL and other human factors have significant impacts on business transactions. Furthermore, the political systems and governmental regulations on business dealings have a lot to do with entrepreneurial success in the international arenas. The study recommends the establishment of a supportive governmental framework to serve as a platform for the willing entrepreneurs to succeed in the international markets. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.